2018
DOI: 10.1097/ijg.0000000000000976
|View full text |Cite
|
Sign up to set email alerts
|

Novel Gonioscopy Score and Predictive Factors for Intraocular Pressure Lowering After Phacoemulsification

Abstract: Preoperative predictors for IOP reduction after cataract surgery were preoperative IOP, ACD, gonioscopy score, and IOP/ACD ratio. The IOP/ACD ratio and gonioscopy score can be easy parameters to obtain and may help clinicians to estimate the IOP reduction after phacoemulsification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Different severity of underlying eye disease may have led to different responses to ECP regardless of anterior or Pars Plana approach. In addition, it is well known that phacoemulsification or vitrectomy may affect IOP . Thus, it is possible that the phacoemulsification frequently performed concomitantly with anterior ECP and the vitrectomy performed concomitantly with ECP‐plus may have affected IOP independent of ECP approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different severity of underlying eye disease may have led to different responses to ECP regardless of anterior or Pars Plana approach. In addition, it is well known that phacoemulsification or vitrectomy may affect IOP . Thus, it is possible that the phacoemulsification frequently performed concomitantly with anterior ECP and the vitrectomy performed concomitantly with ECP‐plus may have affected IOP independent of ECP approach.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is well known that phacoemulsification or vitrectomy may affect IOP. 22,23 Thus, it is possible that the phacoemulsification frequently performed concomitantly with anterior ECP and the vitrectomy performed concomitantly with ECP-plus may have affected IOP independent of ECP approach. Ultimately, a randomized prospective clinical trial is needed to further evaluate the surgical outcome of the two ECP approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the correct lens position, as well as the IOL power obtained using keratometry and axial length values, the ACD must be measured accurately preoperatively. The ACD is particularly important in the diagnosis and treatment of glaucoma patients (16). Yagci et al (17) found that there was an increase in the ACD as well as the ACA in their study results, which revealed an inverse correlation with preoperative values.…”
Section: Resultsmentioning
confidence: 76%
“…All the complementary techniques for imaging the ACA should be better considered as complementary exams to slit-lamp gonioscopy and not as alternatives [ 41 ]. OCT has shown a potential role in predicting the outcome of laser treatments [ 42 , 43 , 44 , 45 ]. Digital gonioscopy has been shown useful in documenting post-operative and abnormal findings of the ACA and has a great potential for teaching gonioscopy.…”
Section: Discussionmentioning
confidence: 99%